On Visual Arts Teachers’ Ideas about Positions of Visual Arts Education in Turkey - Helvacı, İsmail (Elsevier BV, 2013)
AbstractIn this study, the teachers were asked for their opinions in order to determine the effects of new education system introduced in 2012 on visual arts classes. The study is a quantitative research conducted using interview method. The sample of the study includes 12 visual arts teachers working in the center of Kastamonu. The interview questions developed by the researcher were used as a means of data gathering. The findings of the study showed that teachers have negative opinions about the current situation of visual arts classes within the new compulsory education system. The teachers think that visual arts classes are overlooked in the new system; they do not find it right that it is elective for certain grades and they find course hours of compulsory classes inadequate.
Keywords: Teacher; Turkish education system; Art education; 4. Education